China Australia Geological Storage of CO2 (CAGS): Summary of CAGS2 and introducing CAGS3. (July 2017) - Feitz, A.J.; Zhang, J.; Zhang, X.; Gurney, J.
Abstract: The China-Australia Geological Storage of CO2 (CAGS) project was first established in 2008. The project aims to further develop China and Australia's technical skills in the area of geological storage of carbon dioxide (CO2 ) through capacity building activities; training opportunities; sharing of expertise through scientific exchanges; and advancing geological storage science through sponsored research projects in China. Phase 2 was successfully completed in 2015. More than 150 experts, young researchers and students, from over 30 organisations, participated in CAGS2. The project supported 5 research projects, including in the Sichuan Basin, Ordos Basin and in Xinjiang Province. An impact survey revealed strong support for continued engagement from both Australia and China. Participants also commented that participation in CAGS activities had promoted CCS within Chinese institutions and initiated new research activities. The survey also sought ideas and suggestions from participants on research areas that could be explored for future cooperation between Australia and China. Detailed discussions were held at the final workshop on future collaborative opportunities and areas identified include: environmental monitoring; storage site selection; groundwater studies; CCS policy/regulation; and a research program centred on a demonstration project in Xinjiang Province. These recommendations were adopted and form the basis for CAGS3, which continues from 2016 to 2018. A summary of the major activities for CAGS3 is provided.